Low Risk of Cervical Cancer/Precancer Among Most Women Under Surveillance Postcolposcopy. Issue 2 (April 2018) - Demarco, Maria; Cheung, Li C.; Kinney, Walter K.; Wentzensen, Nicolas; Lorey, Thomas S.; Fetterman, Barbara; Poitras, Nancy E.; Befano, Brian; Castle, Philip E.; Schiffman, Mark
Abstract : Objective: To inform impending postcolposcopy guidelines, this analysis examined the subsequent risk of CIN 3+ among women with a grade lower than CIN 2 (< CIN 2) colposcopy results, taking into account the referring results that brought them to colposcopy and cotest results postcolposcopy. Methods: We analyzed 107, 005 women from 25 to 65 years old, recommended for colposcopy at Kaiser Permanente Northern California. We estimated absolute risks of CIN 3+ among women: (1) recommended for colposcopy (precolposcopy), (2) following colposcopy and with histology results < CIN 2 (postcolposcopy), and (3) with cotest results 12 months after a < CIN 2 colposcopy (return cotest). Results: After colposcopy showing < CIN 2 (n = 69, 790; 87% of the women at colposcopy), the 1-year risk of CIN 3+ was 1.2%, compared with 6.3% at the time of colposcopy recommendation. Negative cotest results 1 year after colposcopy identified a large group (37.1%) of women whose risk of CIN 3+ (i.e., <0.2% at 3 years after postcolposcopy cotest) was comparable with women with normal cytology in the screening population. These risks are consistent with current guidelines recommending repeat cotesting 12 months after colposcopy < CIN 2 and a 3-year return for women with a negative postcolposcopy cotest. Conclusions: Most women are at low risk of subsequent CIN 3+ after a colposcopy showing < CIN 2, especially those who are human papillomavirus–negative postcolposcopy, consistent with current management guidelines for repeat testing intervals. Before the finalizing the upcoming guidelines, we will consider additional rounds of postcolposcopy cotesting.